NOVEL PRE-CLINICAL EVIDENCE OF CENTELLA ASIATICA AS CARDIOPROTECTIVE AGENT FOR CARDIOMYOCYTES IN AZITHROMYCIN-INDUCED RATS: A HISTOPATHOLOGICAL PERSPECTIVE - SAKE JULI MARTINA; AZZAHRA WIANA KARTIKA SIREGAR; DWI RITA ANGGRAINI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Azithromycin, a macrolide class of antibiotics, is widely used as a first-line and prophylactic treatment during the COVID-19 pandemic. Despite its therapeutic effects, azithromycin has life-threatening side effects related to the cardiovascular system such as QT-interval prolongation, ventricular arrhythmias, and sudden death. At present, antioxidant agents are needed as cardioprotective agents for cardiac cells to protect against oxidative stress induced by azithromycin. Centella asiatica is one of the natural ingredients currently known to have antioxidant effects. This study aims to evaluate the cardioprotective potential of C. asiatica against azithromycin-induced cardiotoxicity through histopathological examination using routine H and E staining. Methods: This in vivo experimental study involved four groups of Wistar rats treated orally every day for 14 days: K1 (control group), K2 (azithromycin 15 mg/kg body weight [BW]), K3 (azithromycin 15 mg/kg BW+C. asiatica extract 500 mg), and K4 (C. asiatica extract 500 mg). Histopathological staining was used to evaluate myocardial interstitial edema, inflammatory cells, and venous dilatation and congestion. Statistical analyses were performed to evaluate significance. Results: Histopathological results showed significant improvement in myocardial interstitial edema, inflammatory cells, and dilation and congestion of veins in the group treated with C. asiatica following azithromycin induction. A statistically significant difference exists among all groups (p<0.001; Kruskal-Wallis). Statistically significant differences exist across the groups (K1 vs. K2, K1 vs. K3, K2 vs. K3, K2 vs. K4, K3 vs. K4) (p<0.001; Mann–Whitney). No statistically significant difference exists between K3 and K4 for inflammatory cell parameters and venous dilatation and congestion (p>0.05), suggesting that the preventive effect of C. asiatica is nearly equivalent to normal levels. Conclusion: These findings demonstrate the efficacy of C. asiatica as a cardioprotective agent against azithromycin-induced cardiotoxicity.